PENANDA JENIS KELAMIN PADA NAMA JAWA DAN NAMA JERMAN - Wening Sahayu (Faculty of Languages and Arts, Universitas Negeri Yogyakarta, 2014)
AbstractThis study aims to describe gender markers in Javanese and German names. Thedata of Javanese names were collected from family cards in a community in one arearepresenting each regency in Yogyakarta Special Territory. The names were classified bythe gender of the owners. A componential analysis was then carried out to investigatethe gender markers in the names. The discussion on German names and their gendermarkers was based on literature review, including the findings of the studies by Gerhards(2003), Nübling (2009) and Oelkers (2003). German names in the discussion were Vornameor first names. The findings show that there are similarities between Javanese names andGerman names in terms of gender markers. The similarities between them are apparentin: (a) phonetic signs in the form of suffixes, and (b) the number of syllables.